2009
DOI: 10.1242/jeb.022822
|View full text |Cite
|
Sign up to set email alerts
|

Occludin and hydromineral balance inXenopus laevis

Abstract: SUMMARYTo investigate the response of the tight junction (TJ) protein occludin to environmental change in an anuran amphibian, we examined occludin tissue distribution, immunolocalization and alterations in mRNA expression in African clawed frogs (Xenopus laevis) acclimated to brackish water (BW) conditions (from freshwater to 2‰, 5‰ or 10‰ salt water). Occludin mRNA is widely expressed in Xenopus and is abundant in tissues involved in regulating salt and water balance, such as the gastrointestinal (GI) tract,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Despite the fact that many tight junction proteins have been detected in the kidney, their individual role and distribution in the different regions of the fish nephron are unknown. Chasiotis and Kelly, however, showed that occludin was expressed in the distal and not the proximal tubule of goldfish (Chasiotis and Kelly, 2008) and the African clawed frog Xenopus laevis (Chasiotis and Kelly, 2009). Accordingly, rather than indicating a direct reabsorption of protons, the observed H + flux probably represents H + back-flux via the paracellular pathway down the concentration gradient established by active H + secretion into the small closed tubular lumen.…”
Section: General Observationsmentioning
confidence: 90%
“…Despite the fact that many tight junction proteins have been detected in the kidney, their individual role and distribution in the different regions of the fish nephron are unknown. Chasiotis and Kelly, however, showed that occludin was expressed in the distal and not the proximal tubule of goldfish (Chasiotis and Kelly, 2008) and the African clawed frog Xenopus laevis (Chasiotis and Kelly, 2009). Accordingly, rather than indicating a direct reabsorption of protons, the observed H + flux probably represents H + back-flux via the paracellular pathway down the concentration gradient established by active H + secretion into the small closed tubular lumen.…”
Section: General Observationsmentioning
confidence: 90%
“…Ocln is regarded to be an important TJ protein in epithelial barriers (Yu et al, 2005). In Xenopus, Ocln has been shown to exhibit spatial differences in tissue localization that relate to the resistance of epithelia, as well as organ-specific alterations in abundance following changes in the salt content of their surroundings (Chasiotis and Kelly, 2009). Additionally, Ocln is known to undergo post-transcriptional/translational modifications in vertebrates, which remove it from the TJ complex (reviewed in Cummins, 2012).…”
Section: Effect Of Bd Infection On Cldn-1 Ocln and Tric Abundancementioning
confidence: 99%
“…Cldn-1, Ocln, ZO-1), have been shown to respond to changes in environmental conditions (Castillo et al, 1991;Chasiotis and Kelly, 2009;Tokuda et al, 2010). Over 30 genes encoding amphibian TJ proteins have now been reported, yet little is known about their contribution to TJ permeability (Cardellini et al, 1996;Cordenonsi et al, 1997;Fesenko et al, 2000;Klein et al, 2002;Chasiotis and Kelly, 2009;Chang et al, 2010;Saharinen et al, 2010;Yamagishi et al, 2010;Baltzegar et al, 2013;Sun et al, 2015). In addition, the majority of these genes have been identified in the strictly aquatic anurans Xenopus laevis and Xenopus tropicalis; thus, almost nothing is known about the characteristics of TJ proteins in terrestrial and semi-aquatic amphibians (Günzel and Yu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the effects of environmental salinity on the permeability of intestinal epithelia in aquatic vertebrates such as fishes are well documented (see Marshall and Grosell, 2005). In addition, increased permeability of the anterior intestinal epithelium following FW to BW acclimation (without alteration in active transcellular transport processes) has also been suggested to occur in amphibians (Chasiotis and Kelly, 2009). The physiological consequences of decreased NKA and VA activity in the PMG of larval C. riparius in response to IPW rearing are unclear (see Fig.2C, Fig.3C).…”
Section: Differences In Nka and Va Activity In Different Rearing Envimentioning
confidence: 99%